Pengaruh Pengetahuan Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Pada Kantor Samsat Kota Tomohon - Mandagi, Enjelina Novita; Kantohe, Meidy S.S.; Manaroinsong, Johny (Universitas Muhammadiyah Gresik, 2024)
This study aims to find out whether Tax Knowledge and Tax Sanctions Affect the Compliance of Motor Vehicle Taxpayers at the Tomohon City Samsat Office. The research method used in this study is a Quantitative approach. The sample in this study was 100 respondents and was taken using the slovin formula technique. The method used for this study is a survey method with a quantitative approach. In this study, primary data is collected through the distribution of questionnaires. The results of this study show that Tax Knowledge does not have a positive and significant effect on the compliance of motor vehicle taxpayers. Tax sanctions also do not have a positive and significant effect on the compliance of motor vehicle taxpayers at the Tomohon City Samsat Office.